Risk factors and prognosis of silent cerebral infarction after transcatheter aortic valve replacement - Shuguang Wu; Yi Liu; Tingting Ni; Tao Lv; Yuanyuan Yao; Min Yan (Scientific Reports)
Abstract The Valve Academic Research Consortium (VARC)-3 definition of silent cerebral infarction among neurologic events after transcatheter aortic valve replacement (TAVR) lacks clinical validation, yet its impact on postoperative in-hospital outcomes and long-term prognosis remains uncertain. This study aims to explore the perioperative related factors influencing the risk of SCI post-TAVR as defined by VARC-3 criteria, so as to identify high-risk individuals early and assess the effect of SCI on patient outcomes and one-year mortality following TAVR. This was a single-center study including 613 patients with severe aortic stenosis undergoing TAVR, with all data collected prospectively in a dedicated database.We compared clinical baseline data, preoperative imaging results, perioperative factors, and intraoperative variables between patients with and without SCI according to VARC-3. Multivariate logistic regression was used to identify risk factors associated with SCI. Propensity score matching (PSM) at a 1:2 ratio was employed based on fundamental characteristics such as age, gender, BMI, and medical history to minimize potential confounding. Post-matching, we analyzed differences in postoperative in-hospital outcomes and other results between the two groups. Survival times were compared using the Kaplan–Meier method, and survival curves were plotted. The log-rank test assessed statistical differences between the survival curves. Furthermore, univariate and multivariate Cox regression analyses were conducted to determine risk factors for one-year postoperative mortality. Out of 827 TAVR patients screened, 613 were included in the final analysis—471 in the SCI group and 142 in the non-SCI group—resulting in an incidence rate of 76.8% for SCI. The occurrence of post-induction hypotension was significantly higher in the SCI group compared to the non-SCI group (70.28% vs. 61.27%, P = 0.043). Multivariate logistic regression revealed that post-induction hypotension lasting less than 10 min (odds ratio [OR]: 1.73; 95% confidence interval [CI]: 1.13–3.26; P = 0.009), hypotension lasting more than 10 min (OR: 1.98; 95% CI: 1.18–3.33; P = 0.01), and postoperative tachyarrhythmia (OR: 1.98; 95% CI: 1.27–3.07; P = 0.002) were significant risk factors for developing SCI after TAVR. Following 1:2 PSM, 416 patients remained—274 in the SCI group and 142 in the non-SCI group. After matching, the SCI group had a notably higher incidence of postoperative delirium compared to the non-SCI group (9.12% vs. 2.82%; P = 0.017), and their one-year mortality rate was also elevated (5.47% vs. 0.70%; P = 0.016). Additionally, multivariate Cox regression analysis indicated that elevated preoperative creatinine levels (hazard ratio [HR]: 1.01; 95% CI: 1.01–1.02; P = 0.011), presence of SCI (HR: 10.81; 95% CI: 1.31–89.18; P = 0.027), Society of Thoracic Surgeons (STS) score greater than 7% (HR: 3.32; 95% CI: 1.07–10.33; P < 0.038), age 75 years or older (HR: 7.86; 95% CI: 1.01–14.47; P = 0.049), and a history of stroke (HR: 7.20; 95% CI: 2.32–22.35; P < 0.001) were independent risk factors for one-year mortality post-TAVR. Our findings suggest that post-induction hypotension and postoperative tachyarrhythmia are significant risk factors for SCI following TAVR as defined by VARC-3 criteria. Patients who developed SCI after TAVR exhibited higher rates of postoperative delirium and increased one-year mortality compared to those without this complication. Furthermore, factors such as elevated preoperative creatinine levels, an STS score above 7%, age of 75 years or older, and a prior history of stroke were associated with higher one-year mortality rates after TAVR. Given the negative impact of occult SCI on clinical outcomes, every effort should be made to reduce the risk of neurological complications after TAVR.